EVALUASI KESESUAIAN LAHAN TANAMAN UBI JALAR (Ipomoea batatas L.) DENGAN MEMANFAATKAN APLIKASI SPKL DI KECAMATAN CIAMPEA, KABUPATEN BOGOR, JAWA BARAT - Aldila Raffaelia Rosani; Soemarno Soemarno; Yiyi Sulaiman (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Sweet potato plant is one of the food crops that can be utilized by the community to fulfil the need for carbohydrates and vitamins. West Java province as one of the centres of production of this plant is considered to have a good cultivation potential, but lately, it has experienced decreasing land productivity caused by the depreciation of planting areas. The research was conducted in the Sub-district of Ciampea, Bogor, West Java. Research activities were conducted from December 2019 to February 2020. This research was carried out by physiographic method with an analytical approach that utilizes the soil map, where the research location was divided into 12 mapping units as a basis of ground check activities. The land suitability evaluation used the SPKL software application (Land Suitability Assessment System). Results showed that the cultivation of sweet potato in the sub-district of Ciampea was carried out on the marginally suitable lands (S3) and not suitable lands (N) with limiting factors of annual rainfall, land-slope, and soil texture